2018
DOI: 10.1111/wrr.12642
|View full text |Cite
|
Sign up to set email alerts
|

The microbiota of traumatic, open fracture wounds is associated with mechanism of injury

Abstract: Open fractures are characterized by disruption of the skin and soft tissue, which allows for microbial contamination and colonization. Preventing infection-related complications of open fractures and other acute wounds remains an evolving challenge due to an incomplete understanding of how microbial colonization and contamination influence healing and outcomes. Culture-independent molecular methods are now widely used to study human-associated microbial communities without introducing culture biases. Using suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 27 publications
2
29
1
1
Order By: Relevance
“…Similar to burn injury, the wounds created as a result of blunt or penetrating traumas also exhibit changes in skin microbial composition and significant differences in beta diversity compared to controls [ 55 , 56 ]. The microbial composition of open fracture wounds is even associated with mechanism of injury [ 55 ]. The most dominant microbes in open fracture wounds and adjacent skin include Staphylococcus , Corynebacterium , Streptococcus , Acinetobacter , Anaerococcus , Finegoldia , and Pseudomonas .…”
Section: The Cutaneous Microbiome: Aberrations In Human Woundsmentioning
confidence: 99%
“…Similar to burn injury, the wounds created as a result of blunt or penetrating traumas also exhibit changes in skin microbial composition and significant differences in beta diversity compared to controls [ 55 , 56 ]. The microbial composition of open fracture wounds is even associated with mechanism of injury [ 55 ]. The most dominant microbes in open fracture wounds and adjacent skin include Staphylococcus , Corynebacterium , Streptococcus , Acinetobacter , Anaerococcus , Finegoldia , and Pseudomonas .…”
Section: The Cutaneous Microbiome: Aberrations In Human Woundsmentioning
confidence: 99%
“…Intriguingly, numerous studies have shown that wounding can dramatically alter the cutaneous microbiome [ 51 ]; the disruption of skin can lead to bacteria taking advantage of a new environment, a phenomenon termed quorum sensing. This often leads to a reduction in bacterial diversity in chronic wounds [ 52 ], as well as in acute traumatic fracture wounds [ 53 ]. Furthermore, in acute traumatic fracture wounds, wounded tissue has an initially distinct microbiome from nonwounded tissue, but eventually the two converge over the course of healing [ 53 ], suggesting a dynamic role of the microbiome in the wound resolution process.…”
Section: Host–microbe Interactions In the Wound As A Component Of mentioning
confidence: 99%
“…This often leads to a reduction in bacterial diversity in chronic wounds [ 52 ], as well as in acute traumatic fracture wounds [ 53 ]. Furthermore, in acute traumatic fracture wounds, wounded tissue has an initially distinct microbiome from nonwounded tissue, but eventually the two converge over the course of healing [ 53 ], suggesting a dynamic role of the microbiome in the wound resolution process. Significant work has been performed to elucidate how skin flora may either potentiate or impair wound immune responses ( Figure 1 ).…”
Section: Host–microbe Interactions In the Wound As A Component Of mentioning
confidence: 99%
“…diabetic ulcers. Few studies have chronicled the bacteriology of surgical incisions [28][29][30][31] . In this study, we utilized a high-throughput approach to characterize the skin microbiota of adults undergoing colorectal surgery.…”
Section: Introductionmentioning
confidence: 99%